Applied Abhidharma: Personal Transformation through Wisdom, Faith and Grace - Gurung, Pushpa Bahadur (Prajñā Journal of Buddhist Studies, 2026)
The Abhidharma is a systematic and analytical insight into the nature of mind, causality, and morality. This topic focuses on the daily practice of Abhidharma through wisdom, faith, and grace, for personal transformation. It provides an analytical approach to the Buddha's ultimate philosophy, enabling people to adopt a metaphorical, non-theist approach and a soteriological way of understanding that explores how wisdom (Prajñã), faith (Sraddhã), and grace (Anugraha) function to foster personal transformation. In the general approach, the Abhidharma is primarily based on the wandering mind that can be controlled by wisdom. Wisdom cultivates insight into the impermanent and interdependent nature of phenomena, enabling one to overcome ignorance and cultivate a deeper understanding. Additionally, on the other hand, it is not only the systematic and analytical insight into the nature of mind and arrangement of dharmas in numerical order, but it is a faith and grace in God, which elevates the power of the mind by developing the five factors of absorption and its controlling faculties, which are chain-related to faith, energy, mindfulness, concentration, and wisdom. In the non-Buddhist tradition, faith is often regarded as blind adherence, whereas in the Buddhist tradition, faith is understood as confidence in the possibility of achieving success. One’s own mind and effort determine one’s progress and destiny. Mind and effort are the key to self-development. Grace (Anugraha) is not an unmerited gift of God, but rather the beauty of behavior; therefore, it is considered a compassionate support of Buddhas, Bodhisattvas, or the karmic result of personal power through wholesome actions. Through a comparative study of both Pali and Sanskrit Abhidharma traditions, descriptive and interpretive methodological approaches are employed to examine how the Abhidharma doctrine can be applied for personal transformation. This paper outlines moral and existential changes, in which grace actualizes the liberated potential of being, faith sustains drive, and wisdom sharpens understanding.